Implementasi Algoritma Data Mining J48 Untuk Klasifikasi Mahasiswa Yang Layak Mendapat Beasiswa PPA - Buulolo, Ananoma; Bu’ulolo, Efori (Forum Kerjasama Pendidikan Tinggi, 2022)
The PPA Scholarship is a support for educational costs that is given to students who have taken at least semester 2 in Higher Education with consideration of limited economic capacity and have academic and non-academic achievements. In classifying students who are eligible for PPA scholarships, the management has difficulties because the limited PPA scholarships are not proportional to the number of students. One solution in classifying students who are eligible for PPA scholarships is to utilize the data of students who have received PPA scholarships in the previous year. However, in the classification process, data research is needed, one of the data research techniques is data mining. Where data mining is an interesting pattern extraction of large amounts of data [1]. One of the algorithms in data mining used in classification is the J48 algorithm. The J48 algorithm is the implementation of the C4.5 algorithm in the WEKA tools, besides the J48 algorithm is the decision tree implementation in the rapidminer tools. This algorithm is expected to help the management of the PPA scholarship at STMIK Budi Darma in classifying students who really deserve to receive the PPA scholarship. As a result, one of the criteria for a student to be classified as receiving a PPA scholarship is to have achievement